The ANALYSIS OF KALAM IJAZI IN THE STUDY OF BALAGHAH IN QURAN SURAH AL-BAQARAH VERSE 3: Characteristics of the Taqwa - Sarah Mutia; Siti Halija (Yayasan Haiah Nusratul Islam, Indonesia, 2025)
This study aims to analyze the ijazi kalam from the science of balaghah found in the Qur'an, Surah Al-Baqarah, verse three. This verse mentions the characteristics of believers and taqwa people who make the Qur'an their guide in life, namely believing in the unseen, performing prayers, and paying or giving zakat to those who are entitled to receive it. The research method in this article is a descriptive qualitative approach with a literature review as the data and information collection method. The data sources are the Qur'an, Qur'anic exegesis, and previous articles. Ijazi is a short expression that contains a broad meaning. The research results indicate that there is an ijazi statement in Surah Al-Baqarah verse three, specifically in the phrase يؤمنون بالغ. Based on the analysis of the ijazi statement, the meaning of يؤمنون بالغيب is to believe in the unseen, which means believing in Allah, believing in the Prophet Muhammad, and the teachings of Islam.